2010
DOI: 10.1016/j.jvs.2009.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Circulation levels of acute phase proteins in patients with Takayasu arteritis

Abstract: SAA and C4BP may be useful biomarkers in determining the disease activity of TA. More work should be done to test these results in a large cohort of patients in a longitudinal manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…SAA is elevated in adults with both Takayasu arteritis and giant cell arteritis, and correlates with disease activity of inflammatory arteriopathies. 26, 27 …”
Section: Discussionmentioning
confidence: 99%
“…SAA is elevated in adults with both Takayasu arteritis and giant cell arteritis, and correlates with disease activity of inflammatory arteriopathies. 26, 27 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to ESR or serum CRP levels, various other serologic markers, including serum cytokines, matrix metalloproteinases, and serum amyloid A, have been reported to be biologic markers of active TA. [21][22][23] In current clinical practice, no single marker accurately reflects the activity of TA. An autopsy study from India reported that TA disease activity persists for a long time, even in the absence of clinical or laboratory examinations.…”
Section: Discussionmentioning
confidence: 99%
“…In advanced studies, we first evaluated circulation levels of acute phase proteins in TA patients and defined their possibility as biomarkers for activity judgment in this disease. 18 It is also suggested that humoral immunity functional disorder exists in TA patients. Various studies have indicated that TA had a tight relationship with autoimmunity mechanism.…”
Section: Discussionmentioning
confidence: 99%